KAJIAN LITERATUR TENTANG MANFAAT MEDIA PEMBELAJARAN POSTER PADA TEMA "BENDA DISEKITAR KU" UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS III DI SDN DUKUH KUPANG 5 SURABAYA (Adi Widya: Jurnal Pendidikan Dasar, 2024)
The poster learning media on the theme of objects around me for class III students at SDN Dukuh Kupang 5 Surabaya has enormous benefits. The instrument of this literature review consists of several sources such as journals, articles that have been searched. This literature review refers to the journals and articles obtained. Posters have been widely used as learning media. Posters with all their advantages, are able to attract attention and even arouse people who see it. Selection of good posters to increase student creativity will be very helpful in learning, such as the theme of objects around me. Posters have such a high dramatic power to captivate and attract attention. This is because the poster has an adequate description due to psychological factors and is stimulating to live up to. As for the benefits of poster learning media to increase student creativity, encourage meaningful use of subjects by involving imagination and active participation which results in increased learning outcomes, then complementing rich experiences with knowledge that meaningful concepts can be developed. Broaden students' insights and experiences that reflect non-verbalistic learning and make appropriate generalizations, and by using poster learning media students very often hone students' creativity with cycles of always honing posters